Identification of DREB gene family in foxtail millet (Setaria italica) and analysis of its expression pattern in response to abiotic stress - Yang, Yanan; Li, Yun; Guo, Zhenqing; Zhao, Yuxue; Zhou, Xiaoke; Han, Yucui; Lin, Xiaohu (Frontiers in Plant Science, 2025)
Dehydration response element binding proteins (DREBs) play a vital role in transcriptional regulators in enhancing plant tolerance to abiotic stress. To investigate the biological functions of the DREB gene family (SiDREBs) in foxtail millet (Setaria italica), this study performed bioinformatics and gene expression analysis on SiDREBs under abiotic stress. A total of 166 family members of SiDREBs were identified, which were classified into six subfamilies. SiDREBs were unevenly distributed on nine chromosomes, and were designated as SiDREB1–166 based on their chromosomal positions. Covariance analysis revealed that SiDREBs were much more closely related to monocotyledonous plants sorghum, maize, and rice than to dicotyledonous plants Arabidopsis thaliana, tomato, and soybean. Promoter cis-acting element analysis showed that SiDREBs contained stress-related cis-acting elements. Under saline-alkali stress, SiDREB153 exhibited significantly different expression levels between the resistant and susceptible materials, indicating that it plays a positive regulatory role in the response of foxtail millet to saline-alkali stress. Among different abiotic stresses, the expression of SiDREB80 increased under drought, saline-alkali, and shade stress, that of SiDREB4/129/131 rose under saline-alkali and high temperature stress, and that of SiDREB159 increased under herbicide and saline-alkali stress. These genes play an important role in the response of foxtail millet to stress. These findings provide a theoretical basis for further studies on the function of SiDREBs in response to abiotic stress.